Innovation Capability Strategy and Firm Performance in The Furniture Manufacturing Sector in Kenya - Jane Nasimiyu Were (Journal of Economics, Business, and Accountancy Ventura, 2021)
The study sought to examine the contribution of innovation capability in strategy implementation on the firm performance of the furniture manufacturing sector in Kenya. It utilized a descriptive and explanatory research design with a population consisting of 686 managerial staff in the furniture manufacturing sector. The sample of 280 licensed firms was randomly selected by distributing questionnaires to the managers. A factor analysis was used to reduce the number of variables and establish the underlying constructs while analysis of moments of structures was applied to develop theory. It was found that innovation capability had a positive and statistically significant contribution to firm performance. The firm size and firm age were found not to have a moderating effect on the firm performance. The study provides an expansion of the conceptualization of the innovation capability framework. The findings showed that - in order to respond effectively to the business environment that has become so dynamic - firms particularly in the manufacturing sector need to find creative ways of adjusting their strategy implementation tactics in line with changes in the business environment.